ANALISIS PENGARUH BUDAYA ORGANISASI, KOMUNIKASI, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN MINAHASA TENGGARA - Kotangon, Armando Andika; Tewal, Bernhard; Sendow, Greis M. (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: Performance plays an important role in determining the success of a company or organization. Performance is the work result in quality and quantity achieved by an employee in carrying out his duties according to the responsibilities assigned to him. High or good employee performance can be used as one of the basic factors to measure the success of an organization in achieving its goals. This study aims to determine the simultaneous and partial influence of organizational culture, communication, education and training on employee performance, the partial influence of organizational culture on employee performance, the partial influence of communication on employee performance, the partial influence of education and training on employee performance of the District Secretariat. Southeast Minahasa. Respondents in this study amounted to 73 employees who are civil servants. This study uses multiple linear regression analysis. The results of this study simultaneously variable Organizational Culture, Communication, Education and Training together have a significant effect on Employee Performance, then partially the Organizational Culture variable has a positive and insignificant effect on the Performance variable, partially the Communication variable has a positive and insignificant effect on the variable Performance, partially the Education and Training variable has a positive and significant effect on the performance variable.Abstrak: Penelitian ini bertujuan mengetahui pengaruh secara simultan dan parsial budaya organisasi, komunikasi, pendidikan dan pelatihan terhadap kinerja pegawai, pengaruh secara parsial budaya organisasi terhadap kinerja pegawai, pengaruh secara parsial komunikasi terhadap kinerja pegawai, pengaruh secara parsial pendidikan dan pelatihan terhadap kinerja pegawai Sekretariat Daerah Kabupaten Minahasa Tenggara. Responden dalam penelitian ini berjumlah 73 pegawai yang berstatus pegawai negeri sipil. Penelitian ini menggunakan analisis regresi linier berganda. Hasil Penelitian ini secara simultan variabel Budaya Organisasi, Komunikasi, Pendidikan dan Pelatihan secara bersama-sama berpengaruh signifikan terhadap Kinerja Pegawai, kemudian secara parsial variabel Budaya Organisasi berpengaruh positif dan tidak signifikan terhadap variabel Kinerja, secara parsial variabel Komunikasi berpengaruh positif dan tidak signifikan terhadap variabel Kinerja, secara parsial variabel Pendidikan dan Pelatihan berpengaruh positif dan signifikan terhadap variabel Kinerja.